2023
DOI: 10.21608/edj.2023.191453.2425
|View full text |Cite
|
Sign up to set email alerts
|

BioHPP Fixed Hybrid Prosthesis versus BioHPP Bar Overdenture as Treatment Options for Mandibular Edentulous Ridge (Prosthetic Maintenance and Patients’ Satisfaction)

Abstract: Aims: To evaluate prosthetic maintenance and patients' satisfaction with the BioHPP (biocompatible high-performance polymer) was used as a skeletal substructure for the hybrid (implant fixed detachable) prosthesis versus the BioHPP bar supporting and retaining implant overdenture based on the visual analogue scale (VAS). Materials and Methods: twenty completely edentulous male patients were selected randomly from the outpatient clinic of the Department of Prosthodontics, Faculty of Dentistry, Ain Shams Univers… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(9 citation statements)
references
References 36 publications
0
9
0
Order By: Relevance
“…Moreover, there were no significant differences in satisfaction between BioHPP bar-retained overdentures and BioHPP-fixed hybrid prostheses. 33 Overall, CAD-CAM bars had positive outcomes in terms of patient satisfaction with IODs. Different types of bars, including titanium, zirconia, and BioHPPs, offered varying levels of patient satisfaction, ease of oral hygiene, and practitioner preferences.…”
Section: Resultsmentioning
confidence: 91%
See 4 more Smart Citations
“…Moreover, there were no significant differences in satisfaction between BioHPP bar-retained overdentures and BioHPP-fixed hybrid prostheses. 33 Overall, CAD-CAM bars had positive outcomes in terms of patient satisfaction with IODs. Different types of bars, including titanium, zirconia, and BioHPPs, offered varying levels of patient satisfaction, ease of oral hygiene, and practitioner preferences.…”
Section: Resultsmentioning
confidence: 91%
“…Among them, two studies specifically evaluated BioHPP and PEEK bars and reported the occurrence of peri-implantitis as a complication. 33 , 34 Moreover, studies evaluating titanium and zirconia CAD-CAM bars showed fewer biological complications after four and one year of follow-up, respectively. 14 , 17 , 28 , 31 These findings suggest that polymer-based bars, such as BioHPP and PEEK, may be associated with unfavorable biological conditions, including peri-implantitis, after 18 months of follow-up.…”
Section: Resultsmentioning
confidence: 98%
See 3 more Smart Citations